Persistence of Ad26.COV2.S‐associated vaccine‐induced immune thrombotic thrombocytopenia (VITT) and specific detection of VITT antibodies. Issue 5 (21st February 2022) - Kanack, Adam J.; Singh, Bandana; George, Gemlyn; Gundabolu, Krishna; Koepsell, Scott A.; Abou‐Ismail, Mouhamed Yazan; Moser, Karen A.; Smock, Kristi J.; Green, David; Major, Ajay; Chan, Clarence W.; Wool, Geoffrey D.; et al.
Abstract: Rare cases of COVID‐19 vaccinated individuals develop anti‐platelet factor 4 (PF4) antibodies that cause thrombocytopenia and thrombotic complications, a syndrome referred to as vaccine‐induced immune thrombotic thrombocytopenia (VITT). Currently, information on the characteristics and persistence of anti‐PF4 antibodies that cause VITT after Ad26.COV2.S vaccination is limited, and available diagnostic assays fail to differentiate Ad26.COV2.S and ChAdOx1 nCoV‐19‐associated VITT from similar clinical disorders, namely heparin‐induced thrombocytopenia (HIT) and spontaneous HIT. Here we demonstrate that while Ad26.COV2.S‐associated VITT patients are uniformly strongly positive in PF4‐polyanion enzyme‐linked immunosorbent assays (ELISAs); they are frequently negative in the serotonin release assay (SRA). The PF4‐dependent p‐selectin expression assay (PEA) that uses platelets treated with PF4 rather than heparin consistently diagnosed Ad26.COV2.S‐associated VITT. Most Ad26.COV2.S‐associated VITT antibodies persisted for >5 months in PF4‐polyanion ELISAs, while the PEA became negative earlier. Two patients had otherwise unexplained mild persistent thrombocytopenia (140‐150 x 10 3 /µL) 6 months after acute presentation. From an epidemiological perspective, differentiating VITT from spontaneous HIT, another entity that develops in the absence of proximate heparin exposure, and HIT is important, but currently available PF4‐polyanion ELISAs and functional assay are non‐specific and detect all three conditions. Here, we report that a novel un‐complexed PF4 ELISA specifically differentiates VITT, secondary to both Ad26.COV2.S and ChAdOx1 nCoV‐19, from both spontaneous HIT, HIT and commonly‐encountered HIT‐suspected patients who are PF4/polyanion ELISA‐positive but negative in functional assays. In summary, Ad26.COV2.S‐associated VITT antibodies are persistent, and the un‐complexed PF4 ELISA appears to be both sensitive and specific for VITT diagnosis. Abstract :